2014
DOI: 10.5888/pcd11.140186
|View full text |Cite
|
Sign up to set email alerts
|

Dentists’ Self-Perceived Role in Offering Tobacco Cessation Services: Results From a Nationally Representative Survey, United States, 2010–2011

Abstract: IntroductionDental visits represent an opportunity to identify and help patients quit smoking, yet dental settings remain an untapped venue for treatment of tobacco dependence. The purpose of this analysis was to assess factors that may influence patterns of tobacco-use–related practice among a national sample of dental providers.MethodsWe surveyed a representative sample of general dentists practicing in the United States (N = 1,802). Multivariable analysis was used to assess correlates of adherence to tobacc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 21 publications
1
32
2
Order By: Relevance
“…This figure is even lower than that reported recently, which indicated that 11% of smokers receive cessation information from their dentists 11 . In the USA, where smoking cessation services in dental practices are much more established, the rate of referral to specialist services and/or offering cessation prescriptions can be as high as 35% 12 . Higher figures such as these indicate that implementing a smoking cessation referral system among the dental community in Ireland is a worthwhile and achievable goal.…”
Section: References Discussionmentioning
confidence: 99%
“…This figure is even lower than that reported recently, which indicated that 11% of smokers receive cessation information from their dentists 11 . In the USA, where smoking cessation services in dental practices are much more established, the rate of referral to specialist services and/or offering cessation prescriptions can be as high as 35% 12 . Higher figures such as these indicate that implementing a smoking cessation referral system among the dental community in Ireland is a worthwhile and achievable goal.…”
Section: References Discussionmentioning
confidence: 99%
“…Tobacco use is associated with several oral diseases such as periodontal disease, tooth loss, an unsatisfactory response to implants, gingivitis and oral cancer. However, the potential of these professionals in tobacco use control during daily clinical practice remains an unexplored field [7,[17][18][19][20][21].…”
Section: The Role Of Dentists In Tobacco Use Controlmentioning
confidence: 99%
“…In this respect, the possibility of tobacco-dependence education will extend the quality and quantity of interventions and monitoring [7,[9][10][11][12][13]24,28,31,32,[38][39][40].…”
Section: Knowledge About Tobacco Use Treatment and Interventionsmentioning
confidence: 99%
See 2 more Smart Citations